2005
DOI: 10.5713/ajas.2005.516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Combinations of Vitamin A, E and Methionine on Growth Performance, Meat Quality and Immunity in Commercial Broilers

Abstract: The experiment was conducted to study the effect of dietary combinations of vitamin A (VA), vitamin E (VE) and methionine (Met) on growth performance, meat quality and immunity in commercial broilers. Ross chicks (n=3,630) were allocated to five experimental treatments with three replicates per diet. The dietary treatments were:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Vitamin E supplementation of the diet at a dose of 125 ppm was more applicable in increasing the calcium content of tibia as compared to that of 250 ppm, because the supplementation at the two levels did not show significant differences. Lohakare et al (2005) showed that calcium retention was higher when vitamin E was added at higher levels.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E supplementation of the diet at a dose of 125 ppm was more applicable in increasing the calcium content of tibia as compared to that of 250 ppm, because the supplementation at the two levels did not show significant differences. Lohakare et al (2005) showed that calcium retention was higher when vitamin E was added at higher levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that dietary amino acids have important effects on carcass characteristics of broilers (Dozier et al, 2000;Gong et al, 2005;Lohakare, et al, 2005). Moran and Bilgili (1990) and Acar et al (1991) reported live body weight and chilled carcass were not affected by dietary lysine, whereas Tesseraud et al (1999Tesseraud et al ( , 2001 stated that lysine deficiency reduced the performance as well as muscle weights, and breast meat weight decreased when feeding low density of dietary lysine to chicks at 50 d of age (Kidd et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Diets rich in vitamin E and zinc have been shown to reduce the catabolic response induced by immune stimulation and may be effective in promoting growth (Rymer and Givens 2005). Lohakare et al (2004) in an experiment conducted on commercial broiler farm of 3,630 Ross female broiler chicks observed significant (p<0.0001) increase in body weight gain in birds fed higher levels of vitamin E. Chae et al (2005) also reported an improvement in weight gain in commercial broilers supplemented with different levels of vitamin E without affecting the feed efficiency. El-Dein et al (2013) reported better values of Feed conversion ratio (FCR) among chicken supplemented with vitamin E compared to control.…”
Section: Resultsmentioning
confidence: 99%